CORPORATE GOVERNANCE MECHANISMS, INVESTMENT POLICY AND FINANCIAL SUSTAINABILITY OF PENSION FUND ADMINISTRATORS IN NIGERIA - Adeoye Amuda Afolabi; Mubaraq Sanni; Muritala Olatunji Oladele; Yusuf Alabi Olumoh; Muhammed Kamaldeen Usman (Malete Journal of Accounting and Finance)
The pension sector plays a crucial role in ensuring the well-being and financial stability of retirees. Simultaneously, the capacity of pension fund administrators to uphold their financial stability has emerged as a significant global issue. Consequently, this research scrutinized the factors (specifically, corporate governance mechanisms and investment policy) influencing the financial sustainability of Nigerian pension fund administrators. Primary data was gathered through a selfadministered questionnaire following a cross-sectional research design. The study encompassed the 19 pension fund administrators in Nigeria, with a purposively selected sample size of 228. Data analysis was conducted using the PLS-SEM technique. The results revealed that corporate governance mechanisms (β = 0.187, t = 1.046, p = 0.154) and investment policy (β=0.367; t=2.598; and p=0.240) exhibit negligible impacts on the financial sustainability of pension fund managers in Nigeria at 5% level of significance. Consequently, it can be inferred that corporate governance mechanisms and investment policy do not exert a significant influence on the financial sustainability of authorized pension fund administrators in Nigeria. The study recommended that pension fund administrators in Nigeria should regularly assess and update corporate governance procedures to align with industry best practices, implement robust oversight mechanisms to ensure transparency and accountability in decision-making processes, and enhance board training and development to improve the effectiveness of governance structures; and periodically review the investment policy to adapt to changing market conditions and emerging risks, diversify investment portfolios to spread risk and enhance potential returns, and utilize advanced risk management tools to identify and mitigate potential investment risks.